A case-control study of breast cancer and hormonal contraception in Costa Rica - Rosero Bixby, Luis (1987)
By 1981, 11% of married women in Costa Rica ages 20-49 years had used depot-medroxyprogesterone acetate (DMPA) and 58% had used oral contraceptives (OCs). Since 1977, the Costa Rican Ministry of Health has maintained a nationwide cancer registry. These circumstances provided an opportunity for a population-based, case-control study of DMPA, OCs, and breast cancer in Costa Rica. Cases were 171 women ages 25-58 years with breast cancer diagnosed between 1982 and 1984; controls were 826 women randomly chosen during a nationwide household survey. Cases and controls were interviewed with the use of a standard questionnaire covering their reproductive and contraceptive histories. Logistic regression methods were used to adjust for confounding factors. While few cases or controls had ever used DMPA, DMPA users had an elevated relative risk (RR) estimate of breast cancer of 2.6 (95% confidence limits=1.4-4.7) compared with never users. However, no dose-response relationship was found; even the group of women who had used DMPA for less than 1 year had an elevated RR estimate (RR =2.3; 95% confidence limits=1.0-5.1). In contrast, OC users had no elevation in RR compared with never users (RR=1.2; 95% confidence limits= 0.8-1.8). The results of the DMPA analysis are inconclusive. Before decisions are made on whether to continue providing this effective contraceptive method, other ongoing studies will need to confirm of refute these findings.